Clinical prediction of solitary pulmonary nodule after a curative resection for gastric cancer. (15th October 2018) - Kanai, Risa; Tane, Kenta; Ishii, Genichiro; Suzuki, Jun; Sakai, Takashi; Okada, Satoshi; Miyoshi, Tomohiro; Aokage, Keiju; Tsuboi, Masahiro
Abstract : Solitary pulmonary nodule in patients with a history of pathological stage I gastric cancer may be suspected as a primary lung cancer, and an anatomical lung resection should be considered positively. Abstract: Background: Gastric cancer metastasis to the lung can rarely manifest as solitary pulmonary nodule. The surgical strategies are different between metastasis from gastric cancer and primary lung cancer; therefore, the clinical prediction of solitary pulmonary nodule is important. Methods: Between September 2006 and September 2016, 38 patients with a history of curative resection for gastric cancer who subsequently underwent lung resection for solitary pulmonary nodule at our institution were evaluated. We retrospectively reviewed clinical characteristics in order to investigate clinical predictors for diagnosis and appropriate operative strategies. Results: Nodules were shown to be 9 metastasis from gastric cancer, 26 primary lung cancer and 3 benign tumors. Between metastasis from gastric cancer and primary lung cancer, there was a significant difference in age ( P = 0.013), surgical procedure used for gastrectomy ( P = 0.018) and pathological stage of gastric cancer ( P = 0.031). All eight patients who had undergone endoscopic resection for gastric cancer and all 10 patients whose pulmonary nodules were detected more than 5 years after gastrectomy were diagnosed as primary lung cancer. Regarding the prognosis after lung resection, at a median follow-up of 29.3 months, the median survival time in patients with metastasis from gastric cancer was 19.7 months (range, 10.2–63.7 months), whereas that was not reached in patients with primary lung cancer. Conclusions: Solitary pulmonary nodule in patients with a history of pathological stage I gastric cancer may be suspected as primary lung cancer, and an anatomical lung resection should be considered positively. In the case of solitary pulmonary nodule suspected metastasis from gastric cancer from clinical characteristics, a limited resection may be considered, and metastasectomy can potentially result in long-term survival.